SILKFIBROIN-CA-P COMPOSITE BONE REPLACEMENT MATERIAL FOR GUIDED BONE GROWTH - (:unkn) unknown (AALBORG UNIV PRESS, 2015)
Mineralized natural protein based materials are investigated as novel materials to be used in tissue engineering and as bone replacement materials. Silk fibroin fiber based foams and films are used as mineralized composites due to their excellent biocompatibility. In this study, the biomimetic mineralization of orderly oriented fibrous silk based scaffolds was studied. Commercially obtained pure silk woven fabric was boiled in 0.02 M Na2CO3 for 20 min. The deposition of calcium phosphate was conducted at 37 degrees C for twenty minutes in seven sequential immersion steps in 250 mM CaCl2 2H(2)O and 120 mM K2HPO4, both containing 0.15 M NaCl and 50mM solution of TRIS-HCl, buffered at 7.4. Ca-P deposit on the samples increased with the number of immersion steps. The analysis of the Ca-P powder deposit indicated formation of brushite with its characteristic peak at around 11.76 2 theta using the XRD and at 1000, 3000-3500 cm(-1) using the FTIR analyses. Samples were sputter coated with gold for SEM characterization. The morphology of the Ca-P deposits confirmed formation of brushite crystals, which were then transformed into HA using electrochemical hydrothermal treatment in concentrated SBF solution 40 degrees C at a current density of -25mA/cm(2) for 60 min. HA formation was confirmed using XRD, FTIR and SEM analysis. The deposition and electrochemical conversion of brushite to hydroxyapatite on silk, thus forming a silk-HA composite material may be an inexpensive promising biocompatible graft material to be used in bone replacement surgery, where highly oriented materials for guided cell growth may be needed.
Keywords: silk scaffold; hydroxyapatite; composite materials; tissue engineering; bone replacement materials; IN-VITRO; HYDROXYAPATITE; SCAFFOLDS; BIOMATERIALS; CRYSTALS